2008
DOI: 10.1215/15228517-2008-041
|View full text |Cite
|
Sign up to set email alerts
|

Lithium inhibits invasion of glioma cells; possible involvement of glycogen synthase kinase-3

Abstract: Therapies targeting glioma cells that diffusely infiltrate normal brain are highly sought after. Our aim was to identify novel approaches to this problem using glioma spheroid migration assays. Lithium, a currently approved drug for the treatment of bipolar illnesses, has not been previously examined in the context of glioma migration. We found that lithium treatment potently blocked glioma cell migration in spheroid, wound-healing, and brain slice assays. The effects observed were dose dependent and reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 45 publications
10
113
2
Order By: Relevance
“…Recently, 3 independent research groups, including our group, simultaneously reported that GSK3 is a key promoter of malignant GBM phenotypes and is thus a promising candidate for molecular-targeted therapy (Kotliarova et al, 2008;Nowicki et al, 2008;Miyashita et al, 2009a).…”
Section: Gsk3β Biology In Gliomamentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, 3 independent research groups, including our group, simultaneously reported that GSK3 is a key promoter of malignant GBM phenotypes and is thus a promising candidate for molecular-targeted therapy (Kotliarova et al, 2008;Nowicki et al, 2008;Miyashita et al, 2009a).…”
Section: Gsk3β Biology In Gliomamentioning
confidence: 99%
“…The cytotoxic effects are directly correlated with decreased enzymeactivating phosphorylation of GSK3 (Tyr216) (Kotliarova et al, 2008). Furthermore, specific pharmacologic GSK3 inhibitors and siRNA knockdown of GSK3 reduced glioma cell motility (Nowicki et al, 2008). Importantly, administration of a highly specific GSK3 inhibitor, AR-A014418 (Bhat et al, 2003), at a low dose sensitized GBM cells to chemotherapeutic agents such as temozolomide and ionizing radiation, resulting in reduced cell viability (Miyashita et al, 2009a …”
Section: Functionmentioning
confidence: 99%
See 3 more Smart Citations